Self-Reported Juvenile Firesetting: Results from Two National Survey Datasets - Bowling, Carrie H.; Merrick, Joav; Omar, Hatim A. (Frontiers in Public Health, 2013)
The main purpose of this study was to address gaps in existing research by examining the relationship between academic performance and attention problems with juvenile firesetting. Two datasets from the Achenbach System for Empirically Based Assessment (ASEBA) were used. The Factor Analysis Dataset (N = 975) was utilized and results indicated that adolescents who report lower academic performance are more likely to set fires. Additionally, adolescents who report a poor attitude toward school are even more likely to set fires. Results also indicated that attention problems are predictive of self-reported firesetting. The National Survey Dataset (N =1,158) was analyzed to determine the prevalence of firesetting in a normative sample and also examine whether these children reported higher levels of internalizing and externalizing behavior problems. It was found that 4.5% of adolescents in the generalized sample reported firesetting. Firesetters reported more internalizing, externalizing and total problems than their non-firesetting peers. In this normative sample, firesetters were found to have lower academic performance and more attention problems. Limitations include the low overall number of firesetters in each dataset (Factor Analysis n = 123 and National Survey n = 53) and the inclusion of children who had been referred for services in the Factor Analysis Dataset.